Determination of Chaotic Behavior in Liquid Crystal - Ozdemir, Z. Guven; Canli, N. Yilmaz; Ocak, H.; Eran, B. Bilgin (TAYLOR & FRANCIS LTD, 2015)
In this work, chaotic behavior of 4 '-(3,7-dimethyloctyloxy)-4-biphenylcarboxylic acid liquid crystal (LC) has been investigated by Schwarzian derivative method. Determination of negative Schwarzian derivative constitutes a sufficient condition for specifying chaotic behaviors mathematically in nonlinear systems. For this purpose, temperature variation of heat flow experimental data of LC has been utilized. In this context, the chaotic behavior of the LC compound has been investigated by means of the Schwarzian derivative. The chaotic behavior on the transition has been mathematically proved for both heating and cooling procedure.
Keywords: liquid crystal (LC); phase transition; Schwarzian derivative; Chaotic behavior; COMPLEXES; Chemistry; Crystallography; Materials Science